An approach of the educative thought of Blas Roca Calderío (REDEL. Revista Granmense de Desarrollo Local, 2021)
Historical and pedagogical studies are a necessity in Educational Sciences; however, these studies have not received all the attention they deserve. This means that in higher education, particularly in the subject History of Pedagogy, there are difficulties in understanding the evolution and development of educational thought, that is why this article aims to reflect on the educational thought of Blas Roca Calderío, who despite not having exercised the teaching profession for a long period of time, his educational thought contributed to form the generation of Cubans of his time, therefore allowing a better understanding of the development of the educational phenomenon. In carrying out this study, theoretical methods, analytical-synthetic and inductive deductive methods were used, as well as the analysis of documents.
Keywords: educator; educational thinking; educational work